2003
DOI: 10.1080/0891693031000067296
|View full text |Cite
|
Sign up to set email alerts
|

Immunosuppressive Drug Use in Pregnancy

Abstract: Ideally, immunosuppressive drugs would not be necessary in pregnancy. However, in connective tissue disease (especially systemic lupus erythematosus, SLE) vasculitis, and sometimes antiphospholipid antibody syndrome, their use is necessary both to protect the health of the mother and to insure the success of the pregnancy. The more commonly used drugs will be reviewed, with an emphasis on human data, when available. Methotrexate and leflunamide will not be considered, for they should never be used in pregnancy. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0
4

Year Published

2006
2006
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(31 citation statements)
references
References 86 publications
0
27
0
4
Order By: Relevance
“…82 Azathioprine appears in breast milk, and breast feeding is not recommended while taking this drug. 81 However, others feel that the levels of Azathioprine excreted in breast milk are low, and infants have been nursed safely by mothers taking this drug. 80 Cyclosporine is secreted in breast milk, but due to the carcinogenic risk, nursing is generally prohibited even though infants have been reported to have nursed safely by mothers taking cyclosporine.…”
Section: Suggested Guidelinesmentioning
confidence: 99%
See 2 more Smart Citations
“…82 Azathioprine appears in breast milk, and breast feeding is not recommended while taking this drug. 81 However, others feel that the levels of Azathioprine excreted in breast milk are low, and infants have been nursed safely by mothers taking this drug. 80 Cyclosporine is secreted in breast milk, but due to the carcinogenic risk, nursing is generally prohibited even though infants have been reported to have nursed safely by mothers taking cyclosporine.…”
Section: Suggested Guidelinesmentioning
confidence: 99%
“…80 Cyclophosphamide is also excreted in breast milk, and nursing is prohibited while taking this medication due to risk of neonatal leucopenia and potential long-term carcinogenesis. 80,81 No information is available at this time on breast feeding while taking mycophenolate mofetil, but it is recommended not to nurse while on this drug. 80 Postpartum recovery is generally slow for women with lupus, because the mother may have had side effects of corticosteroids (e.g., weight gain), disease effects and due to the increased physical and emotional demands of caring for an infant while having a chronic disease.…”
Section: Suggested Guidelinesmentioning
confidence: 99%
See 1 more Smart Citation
“…Cyclosporine crosses the placental barrier and the newborn blood concentration is 10%-50% of the blood concentration in exposed mothers, but the drug is rapidly eliminated after birth. 23 Two newborns were premature in our cohort but it is difficult to attribute these events to the use of cyclosporine because it has been demonstrated that IBD women have an increase risk of prematurity. A recent metaanalysis has indicated that the relative risk of prematurity is 1.8 and that the incidence of low birth weight is twice that of controls.…”
Section: Discussionmentioning
confidence: 96%
“…It is a selective immunomodulator by acting as a calcineurin inhibitor (22). The drug passively crosses the placental blood barrier to achieve 10 to 50% of the maternal plasma concentration (23). It is not teratogenic in animals or humans.…”
Section: Ciclosporinmentioning
confidence: 99%